IDENTIFIKASI TINGGALAN ARKEOLOGI ERA KOLONIAL BELANDA DI KECAMATAN SUKADANA KABUPATEN CIAMIS: (ANALISIS POTENSI DAN PERMASALAHAN) - Ahmad Rizky Fauzi; Yudi Pauzian; Hasni Hasan (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Sukadana is a sub-district in Ciamis Regency, West Java Province. Since the abandonment of colonial era infrastructure and buildings, quite a few have been neglected because they were not continued and were simply destroyed. There are various types of archaeological remains in the Sukadana District area. This makes the author interested in (1) identifying what archaeological remains are in Sukadana District, (2) what their potential is, (3) what problems and solutions must be implemented. This research is considered important because it is the first research in this area. The research was carried out using qualitative methods, and is descriptive in nature, namely a way of solving problems by providing an overview of the archaeological data found. To solve the problem the author uses the inductive reasoning method. The results of the discussion show that there are many remains of the colonial period in Sukadana District. However, there are many problems faced, such as a lack of concern for the remains themselves. Solutions that can be implemented include intensifying socialization regarding cultural heritage, instilling awareness of historical heritage from an early age and helping to ensure legal certainty of ownership rights to colonial era historical heritage.